Comparison of Chemical Composition and Biological Properties of Essential Oils Obtained by Hydrodistillation and Steam Distillation of Laurus nobilis L - Řebíčková, Kristýna; Bajer, Tomáš; Šilha, David; Ventura, Karel; Bajerová, Petra (Plant foods for human nutrition, 2020)
The purpose of this study was to compare the yield, chemical composition, antimicrobial and antioxidant properties of essential oils isolated from leaves of Laurus nobilis L. by two different distillation methods. The essential oils isolated by hydrodistillation (HD) and steam distillation (SD) were analyzed by gas chromatography coupled to mass spectrometry (GC-MS) and gas chromatography with flame ionization detector (GC-FID). Hydrodistillation produced a yield of 0.95 ± 0.06% which is slightly higher than yield obtained by steam distillation 0.79 ± 0.07%. Seventy three compounds in the bay leaves oil obtained by steam distillation were identified while in essential oil obtained by hydrodistillation were identified only 54 compounds. The antioxidant activity was evaluated by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical method. Antimicrobial activity of obtained essential oils was evaluated by disc diffusion method in comparison with several chosen antimicrobials. The antimicrobial activity was tested on five microorganisms - Escherichia coli, Staphylococcus aureus, Enterococcus faecalis, Pseudomonas aeruginosa and Candida albicans. In general, oils produced by steam distillation had higher antimicrobial and antioxidant activities than hydrodistillation extracts. It seems that hydrodistillation is better for higher yield while steam distillation is better to use for more quality oils with stronger biological properties.
Keywords: destilace; oleje prchavé; Laurus; plynová chromatografie s hmotnostně spektrometrickou detekcí; vavřín; Gas Chromatography-Mass Spectrometry; Distillation; Oils, Volatile; pára; Steam